Subsidy analysis to the forestry sector of the Biobío region, Chile - Mardones Poblete, Cristian; Hernández Cid, Andrea (Instituto de Ecología, A.C., 2017)
The objective of the present study is to evaluate, from an economic and environmental perspective, the impacts of the use of a forest plantation subsidy on economic sectors of the Biobío Region, Chile. The Leontief price model is used to simulate the impacts on sectoral prices, consumption, fiscal expenditure, price index and emissions. The results show that if the subsidy that expired in 2012 was renewed in Chile, prices in the forestry sector would be reduced by 11,74%, while prices in related sectors such as wood and furniture, agriculture, and cellulose and paper, would present reductions of 0,94%, 0,54% and 0,42%, respectively. This would stimulate the production of the forestry sector favoring the capture of emissions of greenhouse gases. In addition, due to the productive linkage, the contribution of the subsidy to the total production of all sectors would be equivalent to 0,11% of regional GDP, based on fiscal expenditure of 0,03% of regional GDP.